Vocational Training and Labour Market l: the Level of National Public Policy - Poviliūnas, Arūnas (Acta Paedagogica Vilnensia, 2004)
The aim of the first of two articles "Vocational Training and Labour Market" is to analyse factors that influence the decision making processes in the field of vocational training on the national level. The first factor is the circulation of information between the systems of vocational training and labour market. The different types of existing information systems that bridge the vocational training and labour market are defined and critically analysed and their impact on national decision making is evaluated. The second factor that ought to have impact in the field of vocational training is strategic priorities of national economy. The critical analysis of long term strategy of development of national economy reveals the lack of strategic priorities that could inform the system of national decision making in the field of vocational training.